The Effect of Organic Manure and Inorganic Fertilizer Application on Carrot Productivity - Seth Niwabiine (Uganda Christian University, 2025)
This study aimed to compare the effects of organic manure and inorganic fertilizer application on carrot yield, with a focus on determining which nutrient source provides better performance in terms of crop productivity and cost-effectiveness. The experiment was carried out using a field experiment under controlled plots having individual treatment of organic manure, inorganic fertilizers, and control without fertilizer application. Important traits under consideration were germination rate, length of the roots, diameter of the roots, total yield, and production expenses. The findings revealed that while inorganic fertilizers resulted in slightly higher yields due to their quick nutrient availability, organic manure significantly improved soil structure and sustained nutrient release, contributing to a more stable and environmentally friendly yield over time. Additionally, organic manure proved to be more cost-effective, especially when sourced locally, offering a viable alternative for resource-limited farmers. The study concluded that integrating organic manure into carrot production not only enhances long-term soil fertility but also provides comparable yield outcomes to inorganic fertilizers, making it a sustainable option for improved agricultural productivity.
UNDERGRADUATE RESEARCH